Odpowiedzi

  • Użytkownik Zadane
2010-02-08T14:38:56+01:00
A-bok kwadratu
d-przekątna kwadratu
d=a√2
a+3=d
a+3=a√2
3=a√2-a
3=a*(√2-1)
a=3/(√2-1)
a=3/(√2-1)*(√2+1)/(√2+1) - usunięcie niewymierności z mianownika
a=3*(√2+1)
P=a²
P=[3*(√2+1)]²
P=3²*(√2+1)²
P=9*(2+√2+1)
P=9*(3+√2)=27+9√2
4 3 4
2010-02-08T14:39:24+01:00
A-bok kwadratu
d-przekątna kwadratu
d=a√2
a+3=d
a+3=a√2
3=a√2-a
3=a*(√2-1)
a=3/(√2-1)
a=3/(√2-1)*(√2+1)/(√2+1) - usunięcie niewymierności z mianownika
a=3*(√2+1)
P=a²
P=[3*(√2+1)]²
P=9*(3+√2)
1 5 1